Analisis Kebutuhan Rohani dan Strategi PAK bagi Remaja Gereja GKE - Triani Cahya Ningsih; Royasefa Ketrin Suek; Jesika Sabatini Ayakeding; Helena Regalia Ujabi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This article examines the spiritual needs of Christian youth and identifies effective ministry strategies for supporting their faith formation. The study explores how child ministry foundations contribute to developing spiritual maturity during adolescence, a phase marked by rapid emotional and social changes. Using a descriptive approach, the discussion highlights core spiritual needs such as identity in Christ, meaningful discipleship, and supportive mentoring environments. The findings suggest that intentional ministry strategies such as relational mentoring, contextualized teaching, and participatory faith practices play a significant role in strengthening the faith and character of young believers. The article concludes that churches and educators must design holistic, youth-centered ministry programs that respond to contemporary challenges while nurturing long-term spiritual growth.